Tingkat Ekonomi dan Motivasi Ibu dalam Pemberian ASI Eksklusif pada Bayi Usia 0-6 Bulan di Bidan Praktek Swasta (BPS) Ummi Latifah Argomulyo, Sedayu Yogyakarta - Heni Maulida; Effatul Afifah; Desiana Pitta Sari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Proﬁle of Indonesian health in 2013 showed that the percentage of exclusive breastfeeding in infants aged 0-6 months is about 61.5%. The low level scope exclusively breastfeeding can not be separated from some factors affecting and one of them is a mother motivation to give exclusively breastfeeding to their baby. The other factors affecting breastfeeding are the socio-culture economy (formal education mother, family income and status working mother). The purpose of this study was to know the relationship between economic level and mother motivation towards exclusive breastfeeding provision in infants aged 0-6 months in BPS Ummi Latifah. This study was an observational analytic with a cross sectional design. Total population are 94 breastfeeding mother. Samples was obtained by accidental sampling techniques which consisted of 48 respondents. Analysis test used kendall-tau (τ). The results showed that the relationship between economic level and mother motivation towards exclusivebreastfeeding provision in infants aged 0-6 months was 0.339 with p=0.007 and coefﬁ cients contingency 0.662. In conclusion, there was a strong relationship between economic level and mother motivation towards exclusive breastfeeding provision in infants aged 0-6 months in BPS Ummi Latifah.